ICT Integrations in TVET: Is it up to Expectations? - Yasak, Zurina; Alias, Maizam (Procedia - Social and Behavioral Sciences, 2015)
In today’s world where information and communication technology is playing a major role in people’s daily lives, how a student learns is dependent on how the student reacts to the sophisticated system offered by these technologies. Thus, it is not surprising that online learning is accepted as an important tool in the general education sector. However its adoption in Technical and Vocational Education and Training (TVET) is yet to reach the equivalence of the general education sector. With the availability of state of the art online learning technology, there is greater opportunity for acquiring the technology that can support TVET practices. The aim of this paper is to discuss the trend of ICT integration in teaching and learning in TVET based on a systematic review of ICT integration in post-secondary TVET. The focus is mainly on the “what’ and “how” aspects of ICT integration in TVET. The literature reviewed indicates that while ICT integration can be aimed at the learning goals in the three domains, the affective, cognitive and psychomotor domain; its effectiveness is more noted where learning goals are of the cognitive domains. More effective integration is also indicated where the blended mode is adopted as compared to the fully ICT mediated mode. Lessons learnt in light of these findings are discussed for future ICT integration in TVET.
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; CLL:en; ICT integration in TVET; Postsecondary Education; Review of ICT role in TVET; publicImportV1